TINJAUAN KUALITAS PUPUK ORGANIK DAN PENGAWASANNYA BAGI KEAMANAN DAN KETAHANAN PANGAN DI INDONESIA - Agustian Agustian (Jurnal Solum, 2010)
The use of organic fertilizers in agricultural production can not only increase soil fertility but also at the same time improve soil quality. Organic fertilizer is a unique product because it can improve physical properties, chemical, and biological soil as plant growth media. These characteristics bring the organic fertilizers into a valuable product that can be used in a variety of use. Today in Indonesia, there are so many outstanding varieties of organic fertilizer products either refined or imported products. Monitoring of the quality and feasibility of organic fertilizer materials is needed, so they will not harm the farmers as consumers. Each country develops criteria standard of organic fertilizer valuing each country's interest. United States, Canada, Australia and Europe use different compost quality criteria tailored to the needs and environmental rules that apply. So far in Indonesia rules used in determining quality is Permentan No. 02/Pert/HK.060/2/2006 which was then updated with Permentan No.28/PERMENTAN/OT.140/2/2009 on Organic Fertilizers and Soil Ameliorant. Basically, the appraisal made on the maturity and quality of organic fertilizers is based on observation of physical, chemical, and biological parameters. Review of the criteria used in the Regulation of the Minister of Agriculture was necessary in considering the criteria used which are very harmful to consumers, such as if it is satated that C-organic content is approximately 12%, which is low, it means that there might exist some follow-up materials such as glass, plastic in the fertilizer about 2%. If the rules are maintained, it will be very detrimental to Indonesia because of invasion from over seas. Import organic fertilizers would be siege to Indonesian farmers. Permentan No.28/PERMENTAN/SR.130/5/2009 has also set up institutions in charge of monitoring the quality of organic fertilizers. However, the quality control must be carried out. It is not only at the level of the end product, but it must also begin from the moment of the production process by establishing a supervisory agency competent. Since organic fertilizers can be produced by large industries, small and medium-scale farmers, the level of supervision is needed with different approaches. Keywords: organic fertilizer, quality, processes and controls